Mathematical Modeling of Strategic Treatments on Tumor Growth (Global Journal of Science Frontier Research, 2014)
We propose to contribute to the emerging body of cancer treatment research by developing and analyzing mathematical models of the treatment of tumor with various strategic treatments. We build on existing models of the immunology that are already successfully developed and then the effects of chemotherapy and interleukin-2 were applied to the model. Thus we build a mathematical model of tumour and effector cell with scheduled chemotherapy.The effect of scheduled il2 dose with chemotherapy and adoptive immunotherapy reduced the tumor growth.
Keywords: mathematical modeling; chemotherapy; effector cell; il-2; adoptive immunotherapy